On the adsorption and reactivity of element 114, flerovium - Yakushev, A.; Lens, L.; Düllmann, Ch. E.; Khuyagbaatar, J.; Jäger, E.; Krier, J.; Runke, J.; Albers, H. M.; Asai, M.; Block, M.; Despotopulos, J.; Di Nitto, A.; et al. (Frontiers in Chemistry, 2022)
Flerovium (Fl, element 114) is the heaviest element chemically studied so far. To date, its interaction with gold was investigated in two gas-solid chromatography experiments, which reported two different types of interaction, however, each based on a level of a few registered atoms only. Whereas noble-gas-like properties were suggested from the first experiment, the second one pointed at a volatile-metal-like character. Here, we present further experimental data on adsorption studies of Fl on silicon oxide and gold surfaces, accounting for the inhomogeneous nature of the surface, as it was used in the experiment and analyzed as part of the reported studies. We confirm that Fl is highly volatile and the least reactive member of group 14. Our experimental observations suggest that Fl exhibits lower reactivity towards Au than the volatile metal, Hg, but higher reactivity than the noble gas, Rn.